Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jcla.22978
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL‐6 level is a prognostic marker in patients with anti‐MDA5 antibody‐positive dermatomyositis associated with interstitial lung disease

Abstract: Objective This study aimed to investigate the clinical significance of Krebs von den Lungen‐6 (KL‐6) serum levels in patients with anti‐MDA5 antibody‐positive dermatomyositis (anti‐MDA5+ DM) having interstitial lung disease (ILD), especially in the amyopathic DM phenotype. Methods The serum KL‐6 level was measured using a chemiluminescence enzyme immunoassay (CLEIA) in patients with anti‐MDA5+ DM, including clinically amyopathic dermatomyositis (CADM)‐ILD and classic DM‐ILD, and healthy donors. The baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
2
32
2
1
Order By: Relevance
“…Our study has revealed a high prevalence of ILD inanti-MDA5 positive patients, consistentwith previous studies in Europeans and Japanese [2,20]. The short-term mortality rate of anti-MDA5 positive patients was especially high within the rst 6-12 months [5,9,13]. Based on these ndings, we set to analyze the rst six months living situation and identify the predictive factors for death in anti-MDA5 positive patients.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our study has revealed a high prevalence of ILD inanti-MDA5 positive patients, consistentwith previous studies in Europeans and Japanese [2,20]. The short-term mortality rate of anti-MDA5 positive patients was especially high within the rst 6-12 months [5,9,13]. Based on these ndings, we set to analyze the rst six months living situation and identify the predictive factors for death in anti-MDA5 positive patients.…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, GGO was a quitecommon pattern in the early stage.Similarly, in a prospective study, patients with GGO in all six lung elds at baselineall died of respiratory failure during follow-up [5]. Fujikiet al [22]also reported the prognosis of patients with right middle lung lobe GGO score≥2 was poor.Different from the wide consensus on the utility ofCT score, the effect o nitial KL-6 level was still controversial in different reports [9,11,13,[21][22][23]. In our cohort, we found the cut off value of initial KL-6>1600U/mlas an independent poor prognostic predictor and the cumulative six-months survival rate differed signi cantly.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Of note, in the study containing all types of myositis, anti-MDA5 has such a strong association with poor prognosis, that it dominates the analysis and makes other potential poor prognostic factors even tend to be a protective factor [11]. While in the subgroup of anti-MDA5 positive patients, the reported risk factors varied in different reports, possibly due to small sample size [5,9,13].…”
Section: Risk Factors Predicting Poor Prognosis Have Been Establishedmentioning
confidence: 98%